Scientific Potential of Enhancing the Integral-Field Spectrometer SPIFFI with a Large Detector and High Spectral Resolution - Eisenhauer, F; Werf, P; Thatte, N; Zeeuw, T; Tecza, M; Franx, M; Iserlohe, C (2001)
SPIFFI is the near-infrared integral-field spectrometer for the VLT. Assisted by the SINFONI adaptive optics module, the instrument will be offered to the astronomical community in 2004. We outline the scientific rationale for infrared integral-field spectroscopy at the VLT, and specifically for the enhancement of SPIFFI with a larger detector and higher spectral resolution gratings. We give examples of a broad variety of astronomical research which will gain specifically from the high angular and spectral resolution provided by SPIFFI, including studies of high red-shift galaxies, merging galaxies, starburst galaxies, superstar clusters, galactic nuclei, extra-solar planets, and circum-stellar discs.